2020
DOI: 10.1016/j.yebeh.2019.106859
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing various sensorimotor and cognitive functions in people with epilepsy is feasible with robotics

Abstract: Background: Epilepsy is a common neurological disorder characterized by recurrent seizures, along with comorbid cognitive and psychosocial impairment. Current gold standards of assessment can quantify cognitive and motor performance, but may not capture all subtleties of behavior. Here, we study the feasibility of assessing various upper limb sensorimotor and cognition functions in people with epilepsy using the Kinarm robotic assessment system. We quantify performance across multiple behavioral domains and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Prior to euthanasia, we assessed the second cohort of animals (~20 min CS) for behavioral comorbidities, as epilepsy is associated with changes in learning, memory, anxiety, depression, and motor coordination [ 123 , 124 , 125 , 126 ]. Importantly, none of these tests, nor brain pathology, showed significant changes in animals treated with SAR on its own (without DFP challenge).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to euthanasia, we assessed the second cohort of animals (~20 min CS) for behavioral comorbidities, as epilepsy is associated with changes in learning, memory, anxiety, depression, and motor coordination [ 123 , 124 , 125 , 126 ]. Importantly, none of these tests, nor brain pathology, showed significant changes in animals treated with SAR on its own (without DFP challenge).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, of note, in the horizontal bar test, all treatment groups improved their time to reach the safety box on the first day compared to the second day, which suggests there was no effect of treatment on motor learning. There is some evidence that epilepsy leads to a change in motor ability, though mostly in children [ 126 , 140 ]. Possibly, there is no change in gross motor behavior in these animals, or the deficits are more present in fine motor skills.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Prior work has demonstrated common bimanual upper limb impairment in individuals with high EDSS (>5.5). 40 …”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that some tasks have a higher than 5% impairment rate for a subset of the control group, 34 however we chose to use a 5% theoretical impairment rate in this study for more convenient comparisons across tasks and because we have reported on a subset of the control groups previously. 34 …”
Section: Methodsmentioning
confidence: 99%
“…Here we use two robotic behavioural tasks-a visually guided reaching task and a bimanual object hitting task-to investigate dominant and non-dominant limb performance in children with DCD. Robotic technology provides an avenue for objective, reliable and accurate assessment of sensorimotor performance 26,27 ; in particular, the visually guided reaching and bimanual object hitting tasks used in the current study have been shown to be clinically valid assessments of motor impairment in adult and pediatric populations with motor difficulties, including stroke [28][29][30] , cerebral palsy 31 , traumatic brain injury 32 and epilepsy 33 . Using robotics, we can examine decision making abilities, motor control and planning abilities as well as dominant, non-dominant and bimanual limb performance, all within a fairly rapid assessment time (10 min).…”
mentioning
confidence: 97%